The Use of Mentimeter to Teach English Vocabulary to 8th Grade in A Private School - Mathilda, Maria Agustin Putri; Ena, Ouda Teda (Language Circle: Journal of Language and Literature, 2023)
English as a compulsory subject taught at various levels of education for students in Indonesia, one of which is at the secondary level. In carrying out English language learning, teachers should build an exciting classroom atmosphere to support the successful implementation of learning in the classroom. The use of media improves students’ understanding of certain concepts that are difficult to explain in verbal language. One media used in teaching and learning is Mentimeter, an interactive web that can allow teachers and students to build interactions as a learning tool.The study was carried out with the subjects of the 8th grade students at one of the private junior high schools in Cilacap. The research aims to identify the students’ problems in learning English vocabulary and to use the Mentimeter application to improve the students’ English vocabulary mastery. The research method used Classroom Action Research. The research shows that the main problems that arose in 8th grade students of one of the private junior high schools in Cilacap were a lack of understanding of English vocabulary and interest in the learning media used by the teacher. After using Mentimeter, the researcher found an increase in students' ability in vocabulary mastery.